METHOD FOR ESTIMATING CONDITION OF SURFACE TREATMENT OF CARBON FELT - OH, EUN-SUN; YE, HEEANG; KIM, SOO-WHAN (2016)
The present invention relates to a method for estimating a condition of surface treatment of a carbon felt, and more specifically, to a method for estimating, with an appropriate level of reproducibility, a heat treatment temperature condition for surface oxidation of a carbon felt. La présente invention concerne un procédé d'estimation d'un état de traitement de surface d'un feutre de carbone, et plus spécifiquement, un procédé d'estimation, avec un niveau approprié de reproductibilité, d'une mise en température de traitement thermique pour l'oxydation de surface d'un feutre de carbone. 본 발명은 카본 펠트의 표면 처리 조건을 추정하는 방법에 관한 것이며, 보다 구체적으로 카본 펠트의 표면 산화를 위한 열처리 온도 조건을 적합한 수준의 재현성을 가지고 추정하는 방법에 관한 것이다.